2023
DOI: 10.1002/ajmg.a.63142
|View full text |Cite
|
Sign up to set email alerts
|

TELO2‐related syndrome (You‐Hoover‐Fong syndrome): Description of 14 new affected individuals and review of the literature

Abstract: You‐Hoover‐Fong syndrome (YHFS) is an autosomal recessive condition caused by pathogenic variants in the TELO2 gene. Affected individuals were reported to have global developmental delay, intellectual disability, microcephaly, dysmorphic facial features, ocular involvement including cortical visual impairment, strabismus, cataract and rotatory nystagmus, movement disorder, hypertonia and spasticity, balance disturbance and ataxia, and abnormal sleep pattern. Other features reported include poor growth, cleft p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Seven genes associated with vision exhibited convergent, relaxed selection, including TELO2, which has been implicated in cortical visual impairment and cataracts (Albokhari et al, 2023), and PCIF1, which has been associated with binocular phenotypes in vertebrates (Bosten et al, 2015). Additionally, in fishes and other vertebrates, the circadian system plays a crucial role in regulating important genes in metabolic pathways, creating a two-way relationship between circadian clocks and metabolic signals (Froland and Whitmore, 2019).…”
Section: Selection Dynamics Of Troglomorphic Candidate Genesmentioning
confidence: 99%
“…Seven genes associated with vision exhibited convergent, relaxed selection, including TELO2, which has been implicated in cortical visual impairment and cataracts (Albokhari et al, 2023), and PCIF1, which has been associated with binocular phenotypes in vertebrates (Bosten et al, 2015). Additionally, in fishes and other vertebrates, the circadian system plays a crucial role in regulating important genes in metabolic pathways, creating a two-way relationship between circadian clocks and metabolic signals (Froland and Whitmore, 2019).…”
Section: Selection Dynamics Of Troglomorphic Candidate Genesmentioning
confidence: 99%
“…Unlike the pleiotropic phenotypes of tel2 mutants in the model organisms described in the early studies, non-lethal mutations in any one of the TTT components mainly cause intellectual disability and neuronal and physical deformities in humans, which is consistent with their interdependency as a single functional unit. Individuals with compound heterozygous of several rare variants such as C367F, D720V, and R609H in Tel2 have been linked to the You-Hoover-Fong syndrome characterized by intellectual disability, global developmental delay, dysmorphic facial features, microcephaly, abnormal movements, and abnormal auditory and visual function [14,15,[127][128][129]. Missense mutations within human Tti2 cause an autosomal recessive disorder defined by intellectual disability, microcephaly, short stature, behavioral problems, skeletal abnormalities, and facial dysmorphic features [16,130,131].…”
Section: Ttt In Disease and Cancer Chemotherapymentioning
confidence: 99%
“…Structural studies have revealed the TTT structure as a single entity or in complex with the R2TP (Rvb1-Rvb2-Tah1-Pih1) [11][12][13], the complex that interacts with Hsp90. A series of mutations have been identified in the TTT that cause the neurodevelopmental syndrome characterized by intellectual disability, global developmental delay, microcephaly, abnormal movements, and various other pathogenic phenotypes [14][15][16][17]. Very recently, Tel2 in the TTT complex has been found to be a target of ivermectin (IVM) [18], an antiparasitic drug that has been successfully used in clinics during the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TELO2 and the R2TP (RUVBL1, RUVBL2, PIH1D1, and RPAP3) complex function in NMD alongside DNA damage signaling [6]. The importance of TELO2-TTI1-TTI2 (TTT) assembly is illustrated by its association with syndromic intellectual disability and You-Hoover-Fong syndrome, which are caused by mutations of TTI1 and TELO2, respectively [14,15]. Loss-of-function variants in the human TELO2 gene have been linked to You-Hoover-Fong syndrome [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of TELO2-TTI1-TTI2 (TTT) assembly is illustrated by its association with syndromic intellectual disability and You-Hoover-Fong syndrome, which are caused by mutations of TTI1 and TELO2, respectively [14,15]. Loss-of-function variants in the human TELO2 gene have been linked to You-Hoover-Fong syndrome [14,15]. Surprisingly, You-Hoover-Fong syndrome patients lack hallmarks of a DNA repair syndrome, such as cancer and premature aging.…”
Section: Introductionmentioning
confidence: 99%